Trade's impact on the labor share: Evidence from German and Italian regions - Claudia M. Buch; Paola Monti; Farid Toubal (Institut für Angewandte Wirtschaftsforschung (IAW), 2008)
Has the labor share declined? And what is the impact of international trade? These questions are not only relevant in an international context they also matter for understanding the regional distribution of incomes in a given country. In this paper, we study two regions with trade exposures that differ from the rest of the country, and which display distinct changes in the labor share. East German and Southern Italian regions have a degree of international openness which is below the countries' averages. At the same time, there has been a more pronounced decline in the labor share in East Germany than in West Germany. In Southern Italy, the labor share has increased in recent years. We show that increased trade openness is not the main culprit behind changing labor shares.
Keywords: E25; F10; R10; 330; labor share; trade; regions; Lohnquote; Außenwirtschaft; Politik der offenen Tür; Regionaler Außenhandel; Neue Bundesländer; Italien (Süd)